SCIENTIFIC AND PRACTICAL APPROACH TO THE ORGANIZATIONAL AND ECONOMIC MECHANISM OF HUMAN CAPITAL MANAGEMENT IN TRADE ENTERPRISES - MOROZOVA, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Human capital is a key determinant of the competitiveness and sustainable development of trade enterprises. In the face of globalization, digital transformation, and structural shifts in the labor market, the effective management of human resources has become increasingly vital. Modern approaches to the development of human capital significantly enhance labor productivity, innovation capacity, and organizational adaptability in a rapidly changing business environment.However, the absence of a unified and industry-specific organizational and economic mechanism for human capital management, coupled with limited digital technology integration and the growing influence of external factors, creates a pressing need for further scientific inquiry and practical innovation. Trade enterprises, in particular, require management models that go beyond generic frameworks, addressing unique challenges such as high employee turnover, operational complexity, and the demand for prompt customer service.This study proposes an integrated organizational and economic mechanism tailored to the specificities of the trade sector. It encompasses economic, organizational, social, informational, and innovative elements, and is designed to respond flexibly to internal and external market conditions. The mechanism supports dynamic HR strategies that include digital tools, personalized motivation systems, and employee development programs aligned with the strategic goals of the enterprise.The benefits of the proposed mechanism include improved HR efficiency, retention of qualified personnel, and the creation of an agile, innovation-driven workforce. By enabling real-time performance monitoring and strategic decision-making, it helps enterprises maintain a competitive edge and achieve long-term objectives. In an era marked by technological disruptions and economic volatility, effective human capital management is not merely a support function but a core driver of business resilience and growth.
Keywords: human capital; personnel management; trade enterprises; organizational and economic mechanism; motivation; digitalization; globalization; innovation; adaptability; competitive advantages, building industry, human capital, innovation, digitalization, social responsibility, strategic planning, supply chain management, adaptation to changes, competitiveness